Impact of Cigarette Smoking on the Gastrointestinal Tract Inflammation: Opposing Effects in Crohn’s Disease and Ulcerative Colitis - Berkowitz, Loni; Schultz, Bárbara M.; Salazar, Geraldyne A.; Pardo-Roa, Catalina; Sebastián, Valentina P.; Álvarez-Lobos, Manuel M.; Bueno, Susan M. (Frontiers in Immunology, 2018)
Cigarette smoking is a major risk factor for gastrointestinal disorders, such as peptic ulcer, Crohn's disease and several cancers. The mechanisms proposed to explain the role of smoking in these disorders include mucosal damage, changes in gut irrigation and impaired mucosal immune response. Paradoxically, cigarette smoking is a protective factor for the development and progression of ulcerative colitis. Ulcerative colitis and Crohn's disease represent the two most important conditions of inflammatory bowel diseases, and share several clinical features. The opposite effects of smoking on these two conditions have been a topic of great interest in the last thirty years, and has not yet been clarified. In this review, we summarize the most important and well-understood effects of smoking in the gastrointestinal tract; and particularly, in intestinal inflammation, discussing available studies that have addressed the causes that would explain the opposite effects of smoking in Crohn's disease and ulcerative colitis.